2021
DOI: 10.3897/mbmg.5.72371
|View full text |Cite
|
Sign up to set email alerts
|

Plankton biodiversity and species co-occurrence based on environmental DNA – a multiple marker study

Abstract: Metabarcoding in combination with high-throughput sequencing (HTS) allows simultaneous detection of multiple taxa by targeting single or several taxonomically informative gene regions from environmental DNA samples. In this study, a multiple-marker HTS approach was applied to investigate the plankton diversity and seasonal succession in the Baltic Sea from winter to autumn. Four different markers targeting the 16S, 18S, and 28S ribosomal RNA genes were employed, including a marker for more efficient dinoflagel… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
15
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 9 publications
(16 citation statements)
references
References 176 publications
1
15
0
Order By: Relevance
“…Interestingly, another toxin-producing dinoflagellate species, Protoceratium reticulatum, was not detected in the samples, although the cysts of this species have been reported from the sediments throughout Tokyo Bay (Matsuoka et al 2003). In a study from the Baltic Sea, the species could be successfully identified from eDNA samples using the same marker (Sildever et al 2021). Thus, the lack of detection in this study could result from collecting data from only a single station, which does not capture the entire diversity of the Bay.…”
Section: Hab Species/genera Detected By Metabarcoding and Hts And By ...mentioning
confidence: 96%
See 3 more Smart Citations
“…Interestingly, another toxin-producing dinoflagellate species, Protoceratium reticulatum, was not detected in the samples, although the cysts of this species have been reported from the sediments throughout Tokyo Bay (Matsuoka et al 2003). In a study from the Baltic Sea, the species could be successfully identified from eDNA samples using the same marker (Sildever et al 2021). Thus, the lack of detection in this study could result from collecting data from only a single station, which does not capture the entire diversity of the Bay.…”
Section: Hab Species/genera Detected By Metabarcoding and Hts And By ...mentioning
confidence: 96%
“…was identified from several samples by metabarcoding and HTS, but had a lower similarity (94%) with the best taxonomic match from the database. Therefore, targeting several genes and usage of genus-specific primers may improve species detection (Gran-Stadniczeñko et al 2017;Nagai et al 2017;Smith et al 2017;Sildever et al 2019Sildever et al , 2021. The low identification of those taxa could also be related to the overall lower number of sequences obtained per sample in 2018 (average 14,508 ± 3,592 sequences after bioinformatics treatment) compared to 2017 (26,781 ± 3,709 sequences after bioinformatics treatment).…”
Section: Hab Species/genera Detected By Metabarcoding and Hts And By ...mentioning
confidence: 99%
See 2 more Smart Citations
“…Cordier et al (2022) [ 18 ] explored the assemblage of 0.24 million eukaryotic ASVs in 1.95 billion DNA reads, representing the plankton diversity in deep-ocean sediments throughout the world. The 18S V9 primers showed potency to locate different species exclusively from the larger assemblage group to the minor fractions, including novel species of phytoplankton, fungi, and zooplankton [ 19 , 20 , 21 ] and different faunal communities [ 22 , 23 , 24 ]. Gut content profiles using eDNA analysis have dramatically increased in the context of taxonomic diversity ecology.…”
Section: Introductionmentioning
confidence: 99%